Bela štorklja Ciconia ciconia - Vrhovnik, Davorin (Acrocephalus, 1998)
Nest from 1994, but nesting successfull only in 1996 and 1998, between Vojnik and Celje
Keywords: bela štorklja; opazovanje; ornithology; ornitologija; Slovenia; Vitanje; Vojnik; White Stork